Co-Rh modified natural zeolites as new catalytic materials to oxidize propane and naphthalene from emission sources - Leguizamón Aparicio, María Silvia del Valle (2016)
Natural zeolites as a raw material to prepare catalytic precursors for the oxidation reaction of linear and poly-aromatic hydrocarbons are reported in this work. The process consisted in the formation of mono- and bi-metallic species containing Co and Co-Rh on natural zeolite tuffs. The materials are analyzed by different physicochemical techniques and used as catalysts for propane and naphthalene oxidation in emissions sources. Comparatively, Rh-zeolites are the most active catalysts for propane conversion. In this case, the formation of mixed oxides seems to be conditioned by surface properties. It could also be suggested that the Rh incorporation on a non-active phase in bimetallic catalysts impacts the effectiveness of the system. In addition, the NO presence increases the activity of bimetallic materials. Rh-Co zeolite systems markedly influence the naphthalene combustion temperature. Whereas in the absence of a catalyst a conversion rate of 50% and 100% is reached at 430 C and 485 °C, respectively. It is interesting to observe that for RhCoCli-Mor and RhCoCli catalyst the 100% conversion is reached at 250 °C.